Simultaneous wavelength and frequency encoded microstructure based quasi-distributed temperature sensor - Li, Xiaolei (2013)
A novel microstructure based temperature sensor system using hybrid wavelength-division-multiplexing /frequency-division-multiplexing (WDM/FDM) is proposed. The sensing unit is a specially designed microstructure sensor both frequency and wavelength encoded, as well as low insertion loss which makes it have the potential to be densely multiplexed along one fiber. Moreover, the microstructure can be simply fabricated by UV light irradiation on commercial single-mode fiber. Assisted with appropriate demodulation algorithm, the temperature distribution along the fiber can be calculated accurately. In theory, more than 1000 sensors can be multiplexed on one fiber. We experimentally demonstrated the feasibility of the scheme through building a sensor system with 9 microstructures multiplexing and with temperature resolution of 0.4°C.